CHARACTERISTICS OF THE CHINESE BOURSES (STOCK MARKETS) - Jarrett, Jeffrey E.; Kyper, Eric (Journal of Advanced Studies in Finance; Vol 3 No 1 (2012): JASF Volume III Issue 1(5) Summer 2012, 2012)
We analyze a data base not heretofore discussed in the literature to determinine some financial characteristics of the Chinese Bourses (Stock Markets). The prupose is to determine if the emerging financial markets of China developed in such a way that here was positive influence associated with technology driven industries. The time period covered and the size of the financials are such that the influence of market anomalies are minimized but the association between closing daily returns for the financial markets are associated with the rise of technology driven industries. In the beginning, we review the growth in financial markets as observed in the growth of financial indicators of the Chinese Bourses. In turn, we study a model to show the relationship between returns and the nature of technology driven industries. Further, we account for the robustness of our final model to remove the effects of autocorrelation in the error term for the estimates equation. We observe some of the financials of each of these industries in noting the distributions of returns by specific industry contain skewness and we observe the differences in these returns as noted the Box Plots of closing returns by industry.